THE INFLUENCE OF PROJECT BASED LEARNING MODEL TO STUDENT'S LEARNING OUTCOMES IN CLASS X OF MACHINARY TECHNIQUE IN PRODUCTION and SHEET METAL WORKING SUBJECT AT SMKN-1 PALANGKA RAYA AT ACADEMIC YEAR 2016/2017 - Setiawan (Jurusan Pendidikan Teknologi Dan Kejuruan, 2017)
Learning model was focused on directional communication resulted in students becoming passive in which they slowly understood the concepts taught by teacher and the learning outcomes obtained by students. They have not reached the minimum mastery criteria (KKM) 70 at the academic year 2016/2017 for course subject of production and sheeet metal working. The purpose of this research is to know the Influence of project based learning model on student learning result of x class of machining technique for course subject of production and sheeet metal working at SMKN-1 Palangka Raya at academic year 2016/2017 The type of this research is quantitative research using sample in the form of pretest result and posttest result in class X SMKN-1 Palangka Raya. The method used in this study is a quasi-experimental method in which its implementation does not use random assignment (random assignment) but by using existing groups. The sample in this study was all students in class X SMKN-1 Palangka Raya divided into experimental class and control class which is class X TPM as experiment class and class X TPL as control class then the total sample is 56 students, consisting of 28 experimental class students and 28 students of control class. The control class implements a conventional learning model while the experimental class uses a project based learning model. Data collection in this research was using test method, documentation and observation. Based on the results of research and data analysis, it can be concluded that the normality test results obtained data prestest and posttest normal distribution, so that the hypothesis test used t-test obtained price tCount>ttable ( 3,45 > 2,005 ). Because tCount = 3,45, it is greater than ttable = 2,005. Then this means H0 rejected, and H1 being accepted which shows that there is the influence of project based learning model on the significant learning outcomes of students on the material of bench and platen in class X of Engineering Technique SMK Negeri 1 Palangka Raya academic year 2016/2017. So it can be concluded that the results of student learning using project-based learning model (Project Based Leraning) is better than the student learning outcomes that use conventional learning model on production and sheeet metal working subject in class X Machinery Engineering at SMK Negeri 1 Palangka Raya.